PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 29 PADANG - Irsyada, Irsyada (Jurnal Edukasi dan Penelitian Matematika, 2024)
Gaining conceptual understanding is one of the goals of education.  However, the results in class VIII of SMP Negeri 29 Padang show that it is at a low stage. The Think-Talk-Write (TTW) cooperative learning model is one way that can be used. Finding out whether eighth graders at SMP Negeri 29 Padang who used the TTW model had a superior understanding of the material compared to those using the direct model was the impetus for this study. This was a quasi-experimental study using a static group design. The sample population consisted of the eighth grade of SMP Negeri 29 Padang. An essay that served as the final exam was the tool used. The t-test was used to analyse the data, and the resulting P-value was 0.040. Thus, H0 was rejected. Using the TTW model, grade eight at SMP Negeri 29 Padang was able to be more effective than using the direct learning model.Keywords – Understanding mathematics concept, TTW, Direct learning